2003
DOI: 10.1038/nature01745
|View full text |Cite
|
Sign up to set email alerts
|

JNK phosphorylates paxillin and regulates cell migration

Abstract: The c-Jun amino-terminal kinase (JNK) is generally thought to be involved in inflammation, proliferation and apoptosis. Accordingly, its substrates are transcription factors and anti-apoptotic proteins. However, JNK has also been shown to be required for Drosophila dorsal closure, and MAP kinase/ERK kinase kinase 1, an upstream kinase in the JNK pathway, has been shown to be essential for cell migration. Both results imply that JNK is important in cell migration. Here we show that JNK1 is required for the rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
442
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(467 citation statements)
references
References 28 publications
22
442
3
Order By: Relevance
“…Moreover, Nek3 siRNA transfectants showed a significant decrease in serine phosphorylation (Figure 5b), implicating Nek3 as a novel kinase in the regulation of paxillin. Both FAK (Ilic et al, 1995;Roy et al, 2002) and JNK (Huang et al, 2003) have been implicated in cell migration and paxillin phosphorylation. However, our analyses have revealed no interaction between FAK and Nek3, and Nek3 overexpression did not increase JNK activity (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Nek3 siRNA transfectants showed a significant decrease in serine phosphorylation (Figure 5b), implicating Nek3 as a novel kinase in the regulation of paxillin. Both FAK (Ilic et al, 1995;Roy et al, 2002) and JNK (Huang et al, 2003) have been implicated in cell migration and paxillin phosphorylation. However, our analyses have revealed no interaction between FAK and Nek3, and Nek3 overexpression did not increase JNK activity (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…JNK kinases are mostly linked with inflammation, proliferation and cell apoptosis, however, they have been also shown to play a role in cell migration. In Drosophila, JNK is required for dorsal closure (Riesgo-Escovar et al, 1996;Sluss et al, 1996), while in zebrafish and rat JNK1 is responsible for the rapid movement of keratocytes and bladder tumour epithelial cells respectively (Huang et al, 2003). Moreover, JNK phosphorylates paxillin, a focal adhesion adaptor, where its role in cell migration is well established.…”
Section: Modulation Of Non-canonical Wnt Pathwaymentioning
confidence: 99%
“…Moreover, JNK phosphorylates paxillin, a focal adhesion adaptor, where its role in cell migration is well established. Mutation in serine residue phosphorylated by JNK causes formation of focal adhesions and limited cell movement indicating that phosphorylation of paxillin by JNK is crucial for labile adhesions facilitating rapid movement (Huang et al, 2003). Furthermore, activation of JNK has been also linked to the expression of metalloproteinase, which are also required during delamination of NC cells (Han et al, 2001).…”
Section: Modulation Of Non-canonical Wnt Pathwaymentioning
confidence: 99%
“…In vitro studies have shown a central role for FAK in different cellular signaling pathways such as cell stress signaling, 28 survival, 12 and proliferation 13 next to its role The location of serine-phosphorylated paxillin and FAs after 2-hour exposure was analyzed by immunofluorescent staining of P Ser178 -paxillin and vinculin, respectively, and followed by confocal laser scanning microscopic analysis. Representative images show the colocalization of vinculin (red) and H 2 O 2 -induced P Ser178 -paxillin (green).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 JNK phosphorylates the FA adapter protein paxillin at serine residue 178 (Ser178). 28 Because FAK is necessary for normal FA turnover, this paxillin phosphorylation site can recruit FAK and therefore is critical for regulation of FA dynamics. 29 We hypothesized that loss of FAK might affect the activation of JNK pathway as well as its interaction with paxillin signaling and, ultimately, affect the FA dynamics after oxidative stress in tubular epithelial cells.…”
Section: Fak Facilitates Activation Of Jnk-associated Fa Recovery Viamentioning
confidence: 99%